The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00784-020-03735-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral tongue leukoplakia: analysis of clinicopathological characteristics, treatment outcomes, and factors related to recurrence and malignant transformation

Abstract: Objectives The tongue is identified as a high-risk site for oral leukoplakia and malignant transformation. The purpose of this study is to investigate the clinicopathological characteristics and treatment outcomes of tongue leukoplakia and assess the factors related to recurrence and malignant transformation. Materials and methods One hundred and forty-four patients who received carbon dioxide laser surgery for tongue leukoplakia from 2002 to 2019 were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
2
7
1
Order By: Relevance
“…In this cohort, the overall cumulative malignant transformation rate and ATR of OL in female patients were 8.22% and 2.08%; while those in male patient were 6.31% and 1.76%, respectively. The ATRs in both genders were similar to the previous reports of OL whose ATRs ranged from 1.08% to 4.90% [15,16,58,60,[64][65][66][67][68][69]. In the Kaplan-Meier survival analysis and log-rank tests, postoperative recurrence was the factor related to malignant change of OL (Hazard ratio: 11.92, CI 95% 2.07-68.67, p = 0.02, Table 4) after laser surgery.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this cohort, the overall cumulative malignant transformation rate and ATR of OL in female patients were 8.22% and 2.08%; while those in male patient were 6.31% and 1.76%, respectively. The ATRs in both genders were similar to the previous reports of OL whose ATRs ranged from 1.08% to 4.90% [15,16,58,60,[64][65][66][67][68][69]. In the Kaplan-Meier survival analysis and log-rank tests, postoperative recurrence was the factor related to malignant change of OL (Hazard ratio: 11.92, CI 95% 2.07-68.67, p = 0.02, Table 4) after laser surgery.…”
Section: Discussionsupporting
confidence: 85%
“…The mean area of the OL with postoperative recurrence (4.81 ± 4.18 cm 2 ) was significantly larger than that of non-recurrent lesions (1.79 ± 2.40 cm 2 ). Not only in the present study, size of area was also a significant factor associated with postoperative recurrence in the studies of oral tongue leukoplakia [58], elderly patients with OL [59], and patients with oral erythroplakia [21]. In addition to being a critical factor related to recurrence, the area of OL was reported to be a risk factor affiliated with malignant change of OL in several studies [11,60,61].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Some authors seemed to use the phrase just to indicate that certain numbers were not represented in the tables or figures but while providing data or results in the same sentence with words; for example: “The ratio of patients showing a history of head and neck cancer (19/47 vs. 14/97, P = 0.0007, data not shown)…” [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, NS, especially non-smoking women, have been consistently reported to be at greater risk of malignant transformation of leukoplakia compared to smoking women [17,31]. In addition to tobacco or smokeless tobacco use, other reported risk factors for malignant transformation of oral leukoplakia included large size, non-homogeneous clinical aspect female sex, old age, location on the tongue or floor of mouth, and high-grade dysplasia [17,32]. We also found that patients with leukoplakia had a significantly improved survival compared to patients with no history of leukoplakia.…”
Section: Discussionmentioning
confidence: 99%